RECONSTRUCTING THE PHILOSOPHY OF ISLAMIC ECO-SOCIAL ENTREPRENEURSHIP: PESANTREN-BASED COASTAL DEVELOPMENT AS A PARADIGM OF ETHICAL TRANSFORMATION - Suyono, Suyono; Fathurrohman, Fathurrohman; Fuady, Ahmad Silmul; Huda, Miftachul (Jurnal Al-Ijtimaiyyah, 2026)
The structural paradox of coastal poverty in Muslim-majority communities lies in abundant marine resources alongside economic marginalization and environmental degradation. While Islamic institutions have historically contributed to social welfare, their role in contemporary sustainability discourse remains underexplored. This study examines pesantren-based coastal development as a model of ethical transformation to reconstruct the philosophical foundations of Islamic eco-social entrepreneurship. Using a thematic and interpretative analysis, the findings reveal that pesantren function as socio-economic catalysts beyond their religious roles. Santri-led enterprises diversify livelihoods, reduce reliance on exploitative middlemen, and promote environmentally responsible practices such as sustainable fishing and waste management. Triangulated data indicate a shift from exploitative to conservation-oriented behavior. The model is grounded in three dimensions: khilafah (ecological stewardship), integration of religious knowledge and skills, and commitment to maslahah and mizan. This integrative approach positions pesantren as ethical-economic actors, redefining poverty alleviation as moral-ecological reconstruction within a sustainable Islamic development paradigm.